ELECTRON DENSITY CALCULATINS OF COMPLEX MOLECULES - MAHMOOD, HAMD (Fırat Üniveristesi, 2017)
Bu tez çalışmasında bazı molekülerin electron yoğunlukları DFT metodu ile hesaplandı. Ayrıca aynı sistemlerin moleküler orbittaleri ve FTIR spektromları da DFT metodu ile hesaplandı. Bütün sonuçlar detaylı olarak yorumlandı.

FTIR spectroscopy is related to the vibration modes of a molecule. To calculate the vibrational modes, electron density functions and molecular orbitals density function theory (DFT) method was applied. In this master thesis, we have calculated infrared spectroscopy, electron densities and molecular orbital for many different big molecules by implementing DFT method. All the results were interpreted in detail.
Kompleks moleküllerin elektron yoğunluğunun hesaplanması
Keywords: Fizik ve Fizik Mühendisliği